Thermoelectric Coolers: Progress, Challenges, and Opportunities. Issue 2 (5th January 2022) - Chen, Wen‐Yi; Shi, Xiao‐Lei; Zou, Jin; Chen, Zhi‐Gang
Abstract: Owing to the free of noise, mechanical component, working fluid, and chemical reaction, thermoelectric cooling is regarded as a suitable solution to address the greenhouse emission for the broad cooling scenarios. Here, the significant progress of state‐of‐the‐art thermoelectric coolers is comprehensively summarized and the related aspects of materials, fundamental design, heat sinks, and structures, are overviewed. Particularly, the usage of thermoelectric coolers in smart city, greenhouse, and personal and chip thermal management is highlighted. In the end, current challenges and future opportunities for further improvement of designs, performance, and applications of thermoelectric coolers are pointed out. Abstract : This review aims to summarize the significant progress of state‐of‐the‐art thermoelectric coolers (TECs) from aspects of TEC‐based materials, fundamental design rules, heat sinks, structures, and wide applications. The current challenges and future opportunities for further improvement of designs, performance, and applications of TECs are also provided.